NEPHROPROTECTION OF PIGEON PEA ( CAJANUS CAJAN ( LINN.) HUTH) AGAINST GENTAMYCIN-INDUCED NEPHROTOXICITY IN WHITE MALE RATS WISTAR STRAIN ( RATTUS NOVERGICUS) - Rahayuningsih, Nur (P3M STIKes Bakti Tunas Husada, 2020)
Pigeon pea (Cajanus cajan (Linn.) Huth) is a family of plant species, Leguminoceae can provide Nephroprotection based antioxidant effect. The purpose of this study was to determine the activity of pigeon pea as Nephroprotection on white male rats Wistar strain (Rattus novergicus) with the induction of gentamicin were seen from the levels Creatinine, Blood Urea Nitrogen and a picture of rat kidney histopathology. This research is the true experimental use of white male rats Wistar strain were divided into 5 groups randomly. The first group was normal control, group II negative control (gentamicin 60 mg/kg rats i.p and CMC 1% orally), Group III, IV and V (pigeon pea dose of 100 mg/kg, 200 mg/kg and 400 mg/kg rats in CMC 1% orally and then 2 hours after administration of the test dose followed by induction of gentamicin 60 mg/kg rats intraperitoneal) for 7 days. The results of Statistical analysis showed that pigeon pea can lower creatinine levels (p <0.05) and may protect the kidney cell necrosis. But there is no effect on the level BUN p=0.795. The effectiveness of Nephroprotection was best produced in dose II (200 mg/kg) because it can reduce creatinine levels and repair necrosis cell 19.608